Pengoptimalan Komunikasi Bahasa Isyarat Abjad dengan Augmented Reality - Syamsumar Bustamin; Hamdani, Ibnu Mansyur (Jurnal PROCESSOR, 2023)
One of the activities that humans always do is communication. This communication is carried out by everyone, but there are special ways of communication that are carried out by people with special needs, such as the deaf. The communication uses sign language, where learning the language is quite difficult, especially for students who are deaf. There is a solution that can solve this problem, namely the use of technology. One of the technologies that can be used is Augmented Reality. Augmented Reality is able to combine the physical world and digital elements that can be used to facilitate human activities. Augmented Reality is designed and packaged in the form of a mobile-based application to make it easier to learn sign language. The use of this designed application is specifically aimed at students with special needs. In addition, the use of the application can also be felt by a group of people who are learning sign language. Application testing involves various aspects, such as functional testing, device compatibility testing, performance testing, AR accuracy and compatibility testing, interaction testing, usability testing, and testing in real environments. App testing engages users, either in user testing or through the feedback they provide. The users involved are divided into 2, namely users as experts in AR testing and users as customers or in this case teachers. The test results prove the value with a high percentage. Tests by experts achieve an average value of 93.13% and tests by customers achieve an average value of 93.60%. This average value can be classified as a reference that the application functions properly, according to needs, is safe, responsive, and provides a satisfying experience.